2010
DOI: 10.1371/journal.pone.0012837
|View full text |Cite
|
Sign up to set email alerts
|

Bone Is Not Essential for Osteoclast Activation

Abstract: BackgroundThe mechanism whereby bone activates resorptive behavior in osteoclasts, the cells that resorb bone, is unknown. It is known that αvβ3 ligands are important, because blockade of αvβ3 receptor signaling inhibits bone resorption, but this might be through inhibition of adhesion or migration rather than resorption itself. Nor is it known whether αvβ3 ligands are sufficient for resorption the consensus is that bone mineral is essential for the recognition of bone as the substrate appropriate for resorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 58 publications
1
36
0
Order By: Relevance
“…However, some ECM proteins were found to be more favourable than others. Vitronectin is the preferential matrix for podosome formation in osteoclasts (Fuller et al, 2010) whereas fibrinogen is the best for macrophages (Labernadie et al, 2010). We have now found that laminin and Col-IV are the preferential substrates for podosome induction in HMVECs.…”
Section: Discussionmentioning
confidence: 64%
“…However, some ECM proteins were found to be more favourable than others. Vitronectin is the preferential matrix for podosome formation in osteoclasts (Fuller et al, 2010) whereas fibrinogen is the best for macrophages (Labernadie et al, 2010). We have now found that laminin and Col-IV are the preferential substrates for podosome induction in HMVECs.…”
Section: Discussionmentioning
confidence: 64%
“…We have shown that their formation is substrateexclusive, meaning that the SZ forms only on mineralized substrates such as bone or hydroxyapatite-coated glass. 90 However, Fuller et al (2010) have provided experimental data indicating that the SZL, observed on glass or plastic, is associated with the same functional changes as the SZ, and the difference between the two structures might be attributable to the greater spreading caused by smooth surfaces. 93 The overall transition from clusters to SZs is marked not only by a collective displacement of podosomes but also by different internal actin dynamics and increased interconnectivity between podosomes (Fig.…”
Section: Podosome Patterning In Osteoclastsmentioning
confidence: 99%
“…Indeed, while previous investigations of OC adhesion have been performed on culture-treated substrates, it has been shown that OCs can adhere when seeded on a substrate, which does not allow podosome formation, i.e., devoid of either integrin ligands or more specifically αvβ3 integrin ligand. 75,93 Ring-driven saltatory migration An adherent and fully spread OC forms podosomes that grow in a confined space during their assembly phase. The growth of podosomes in close vicinity within a cluster leads to them "pushing" each other, thus resulting in a ring pattern.…”
Section: Podosome Patterning In Osteoclastsmentioning
confidence: 99%
“…Given no clear evidence of osteoclast resorption and depleted Ca 2+ /P i levels in the conditioned medium, we speculate that the osteogenic effects were most likely due to osteoclast-secreted trophic factors in response to the submicrostructured surface topography. In a broader biological context, it is pertinent to note that non-resorbing osteoclasts have been identified as a source of osteogenic factors in vivo (Karsdal et al, 2007;Karsdal et al, 2008;Kreja et al, 2010), emphasising that resorption is not necessary for osteogenic signalling (Fuller et al, 2010), potentially an interesting link for non-resorbable, osteoinductive materials such as microstructured titanium. Concerning the interspecies potency of the osteogenic factors demonstrated here, Pederson et al (2008) first reported that RAW264.7 osteoclast-like cells secrete soluble sphingosine 1 phosphate (S1P) and BMP6 which can differentiate hMSC into mineralising osteoblasts.…”
Section: Nl Davison Et Al Surface Architecture Of Tricalcium Phosphatementioning
confidence: 99%